(untitled) (Research, Society and Development, 2022)
The biopolymer coating use on seeds has aroused the interest of the agricultural sector due to its low cost, reduction of impacts on the environment and improvements in productivity and yield of major crops, being chitosan an important polymer for application in seeds. Considering this knowledge, the present study aimed to evaluate the application effect of a bioproduct based on chitosan, from the parameters of physiological quality, vigor, and biochemistry in tobacco seeds. Seeds of the Virginia variety were submitted to treatments: 0.0 (witness); 0.5; 1; 2.5; 5; and 10% were used to obtain first count values, germination test, seedling length and fresh mass, and chlorophyll and carotenoid contents. The bioproduct had a positive effect on chlorophyll a, b, and carotenoids at 10% FTSeed concentration and seedling length under 5.25% FTSeed. The study pointed out that the bioproduct has a favorable action on the development and leaf pigments, being an alternative biostimulant with less impact on the environment for the agricultural sector.